Tailoring the molecular and thermo–mechanical properties of kraft lignin by ultrafiltration. Issue 18 (21st April 2014) - Sevastyanova, Olena; Helander, Mikaela; Chowdhury, Sudip; Lange, Heiko; Wedin, Helena; Zhang, Liming; Ek, Monica; Kadla, John F.; Crestini, Claudia; Lindström, Mikael E.
ABSTRACT: This study has shown that ultrafiltration allows the selective extraction from industrial black liquors of lignin fraction with specific thermo‐mechanical properties, which can be matched to the intended end uses. Ultrafiltration resulted in the efficient fractionation of kraft lignin according to its molecular weight, with an accumulation of sulfur‐containing compounds in the low‐molecular weight fractions. The obtained lignin samples had a varying quantities of functional groups, which correlated with their molecular weight with decreased molecular size, the lignin fractions had a higher amount of phenolic hydroxyl groups and fewer aliphatic hydroxyl groups. Depending on the molecular weight, glass‐transition temperatures ( Tg ) between 70 and 170°C were obtained for lignin samples isolated from the same batch of black liquor, a tendency confirmed by two independent methods, DSC, and dynamic rheology (DMA). The Fox–Flory equation adequately described the relationship between the number average molecular masses ( Mn ) and Tg 's‐irrespective of the method applied. DMA showed that low‐molecular‐weight lignin exhibits a good flow behavior as well as high‐temperature crosslinking capability. Unfractionated and high molecular weight lignin ( Mw >5 kDa), on the other hand, do not soften sufficiently and may require additional modifications for use in thermal processings where melt‐flow is required as the first step. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40799. Abstract :